1979
DOI: 10.1093/infdis/139.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Meningitis with Use of Selected Clinical Data and Gas-Liquid Chromatographic Determination of Lactate Concentration in Cerebrospinal Fluid

Abstract: The usefulness of determination of lactate concentration in cerebrospinal fluid (CSF) for differentiation between various types of meningitis was evaluated. Lactate concentration in the CSF was assayed by gas-liquid chromatography for 115 patients, 17 of whom had serous meningitis and 38 had bacterial meningitis. The mean lactate concentration in the CSF of patients with bacterial meningitis was significantly higher than in the CSF of patients with serous meningitis and in a control group. The mean concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 8 publications
0
8
1
2
Order By: Relevance
“…This is in contrast to the usual findings of normal lactate concentrations in viral meningitis (19)(20)(21)(22)(23)(24)(25)(26)(27). CSF lactate concentrations are also increased in fungal meningitis.…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studicontrasting
confidence: 65%
“…This is in contrast to the usual findings of normal lactate concentrations in viral meningitis (19)(20)(21)(22)(23)(24)(25)(26)(27). CSF lactate concentrations are also increased in fungal meningitis.…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studicontrasting
confidence: 65%
“…A total of 90 articles were excluded from final analysis due to the following reasons: (1) comment/review/guidelines/reply/case report ( n = 22), (2) non-English language ( n = 1), (3) no lactate concentration ( n = 7), (4) no BM or AM group ( n = 20), (5) in vitro or animal research ( n = 3), (6) unable to exclude partially treated patients ( n = 6), (7) unable to extract data ( n = 11), and (8) low number of participants ( n = 20). Finally, 25 studies were selected for final analysis [11,12,37-58] with agreement between the two reviewers (κ = 0.898).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies [11,12,38,39,41-43,46-56,59] that analyzed only diagnosed BM and five other studies [37,40,44,45,57] that included diagnosed BM as well as clinical BM that could be extracted separately were included in the subgroup analysis. The specificity and LR+ were heterogeneous among the studies, but sensitivity, LR-, and DOR were significantly homogenous (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations